Safety, immunogenicity and dose response of VLA84, a new vaccine candidate against Clostridium difficile, in healthy volunteers. Issue 23 (17th May 2016) - Bézay, Nicole; Ayad, Andrea; Dubischar, Katrin; Firbas, Christa; Hochreiter, Romana; Kiermayr, Sigrid; Kiss, István; Pinl, Fritz; Jilma, Bernd; Westritschnig, Kerstin
Highlights: A new vaccine candidate VLA84 to prevent CDI has been tested in a Phase I trial. VLA84 was safe and well tolerated in healthy adult and healthy elderly volunteers. VLA84 was highly immunogenic in adults and elderly. IgG antibodies persisted at least 6 months after last immunization. Functionality of IgG antibodies was shown in a T84 toxin neutralization assay. Abstract: Background: Clostridium difficile infection (CDI) is the leading cause of antibiotic-associated diarrhoea and colitis and the most common pathogen of health care-associated infections. In the US, CDI causes approximately half a million infections and close to 30, 000 deaths. Despite antibiotic treatment of C. difficile associated diarrhoea, the disease is complicated by its recurrence in up to 30% of patients. Methods: An open-label, partially randomized, dose-escalation Phase I trial was performed in two parts. Sixty volunteers aged ≥18 to <65 years were randomized into five treatment groups to receive three immunizations (Day 0, 7, 21) of VLA84 (20 μg with Alum, 75 μg with or without Alum, 200 μg with or without Alum). Eighty-one volunteers aged ≥65 were randomized into four treatment groups (75 μg with or without Alum, 200 μg with or without Alum) and received four immunizations (Day 0, 7, 28 and 56). All subjects were followed for safety and immunogenicity for six months. Results: VLA84 was safe and well tolerated. Fifty-one adult volunteers (85%) and 50 elderly (62%) experienced at least one solicited or unsolicited adverse event (AE). Forty-eight adult volunteers (80%) and 40 elderly (49%) experienced related AEs which were mostly mild or moderate. No related serious adverse event and no death occurred. The vaccine induced high antibody titres against Toxin A and Toxin B in both study populations. Conclusion: VLA84 was safe, well tolerated and highly immunogenic in adult volunteers aged ≥18 to <65 years and elderly volunteers aged ≥65 years. This study is registered at ClinicalTrials.gov under registration numberNCT01296386 .